Accessory and Central α-helices of Complexin Selectively Activate Ca2+ Triggering of Synaptic Exocytosis - Yu, Yi; Chen, Su; Mo, Xiaoqiang; Gong, Jihong; Li, Chenhong; Yang, Xiaofei (Frontiers in Molecular Neuroscience, 2018)
Complexins, binding to assembling SNARE complexes, activate Ca2+ triggered exocytosis and clamp spontaneous release in the presynaptic terminal. Functions of complexin are structural dependent and mechanistically distinct. To further understand the functional/structural dependence of complexin, here we show that the accessory and central α-helices of complexin are sufficient in activation of Ca2+ triggered vesicle fusion but not in clamping spontaneous release. Targeting the two α-helices to synaptic vesicle suppresses spontaneous release, thus further emphasizing the importance of curvature membrane localization in clamping function.